Access to and sustainability of abortion services: a systematic review and meta-analysis for the National Institute of Health and Care Excellence—new clinical guidelines for England. (26th July 2020) - O'Shea, Laura E; Hawkins, James E; Lord, Jonathan; Schmidt-Hansen, Mia; Hasler, Elise; Cameron, Sharon; Cameron, Iain T
Abstract: BACKGROUND: Induced abortion is a common procedure. However, there is marked variation in accessibility of services across England. Accessing abortion services may be difficult, particularly for women who live in remote areas, are in the second trimester of pregnancy, have complex pre-existing conditions or have difficult social circumstances. OBJECTIVE AND RATIONALE: This article presents a two-part review undertaken for a new National Institute of Health and Care Excellence guideline on abortion care, and aiming to determine: the factors that help or hinder accessibility and sustainability of abortion services in England (qualitative review), and strategies that improve these factors, and/or other factors identified by stakeholders (quantitative review). Economic modelling was undertaken to estimate cost savings associated with reducing waiting times. SEARCH METHODS: Ovid Embase Classic and Embase, Ovid MEDLINE(R) Epub Ahead of Print, In-Process & Other Non-Indexed Citations, Ovid MEDLINE(R) Daily and Ovid MEDLINE(R), PsycINFO, Cochrane Library via Wiley Online, Cinahl Plus and Web of Science Core Collection were searched for articles published up to November 2018. Studies were included if they were published in English after 2001, conducted in Organization for Economic Co-operation and Development (OECD) countries and were: qualitative studies reporting views of patients and/or staff on factors that help or hinder the accessibility and sustainability of a safe abortion service, or randomized or non-randomized studies that compared strategies to improve factors identified by the qualitative review and/or stakeholders. Studies were excluded if they were conducted in OECD countries where abortion is prohibited altogether or only performed to save the woman's life. One author assessed risk of bias of included studies using the following checklists: Critical Appraisal Skills Programme checklist for qualitative studies, Cochrane Collaboration quality checklist for randomized controlled trials, Newcastle-Ottawa scale for cohort studies, and Effective Practice and Organization of Care risk of bias tool for before-and-after studies. Qualitative evidence was combined using thematic analysis and overall quality of the evidence was assessed using Grading of Recommendations, Assessment, Development and Evaluations (GRADE) Confidence in the Evidence from Reviews of Qualitative Research (CERQual). Quantitative evidence was analysed in Review Manager 5.3 and overall quality of evidence was assessed using GRADE. OUTCOMES: Eight themes (service level barriers; financial barriers; logistical barriers; personal barriers; legal and policy barriers; privacy and confidentiality concerns; training and education; community prescribing and telemedicine introduce greater flexibility) and 18 subthemes were identified from 23 papers (n = 1016) included in the qualitative review. The quality of evidence ranged from very low to high, with evidence for one theme and seven subthemes rated as high quality. Nine studies (n = 7061) were included in the quantitative review which showed that satisfaction was better (low to high quality evidence) and women were seen sooner (very low quality evidence) when care was led by nurses or midwives compared with physician-led services, women were seen sooner when they could self-refer (very low quality evidence), and clinicians were more likely to provide abortions if training used an opt-out model (very low quality evidence). Economic modelling showed that even small reductions in waiting times could result in large cost savings for services. WIDER IMPLICATIONS: Self-referral, funding for travel and accommodation, reducing waiting times, remote assessment, community services, maximizing the role of nurses and midwives and including practical experience of performing abortion in core curriculums, unless the trainee opts out, should improve access to and sustainability of abortion services.